Intratumoral immunotherapy using a TLR2/3 agonist, L-pampo, induces robust antitumor immune responses and enhances immune checkpoint blockade. Issue 6 (28th June 2022) - Lee, Won Suk; Kim, Dong Sung; Kim, Jeong Hun; Heo, Yoonki; Yang, Hannah; Go, Eun-Jin; Kim, Jin Hyoung; Lee, Seung Joon; Ahn, Byung Cheol; Yum, Jung Sun; Chon, Hong Jae; Kim, Chan
Abstract : Background: Toll-like receptors (TLRs) are critical innate immune sensors that elicit antitumor immune responses in cancer immunotherapy. Although a few TLR agonists have been approved for the treatment of patients with early-stage superficial cancers, their therapeutic efficacy is limited in patient with advanced invasive cancers. Here, we identified the therapeutic role of a TLR2/3 agonist, L-pampo (LP), which promotes antitumor immunity and enhances the immune checkpoint blockade. Methods: We generated LP by combining a TLR2 agonist, Pam3CSK4, with a TLR3 agonist, Poly (I:C). Immune responses to stimulation with various TLR agonists were compared. Tumor-bearing mice were intratumorally treated with LP, and their tumor sizes were measured. The antitumor effects of LP treatment were determined using flow cytometry, multiplexed imaging, and NanoString nCounter immune profiling. The immunotherapeutic potential of LP in combination with α-programmed cell death protein-1 (PD-1) or α-cytotoxic T-lymphocytes-associated protein 4 (CTLA-4) was evaluated in syngeneic MC38 colon cancer and B16F10 melanoma. Results: The LP treatment induced a potent activation of T helper 1 (Th1) and 2 (Th2)-mediated immunity, tumor cell apoptosis, and immunogenic tumor cell death. Intratumoral LP treatment effectively inhibited tumor progression by activating tumor-specific T cell immunity. LP-induced immune responses were mediated by CD8 + T cells and interferon-γ, but not by CD4 + T cells and CD25 + T cells. LP simultaneously activated TLR2 and TLR3 signaling, thereby extensively changing the immune-related gene signatures within the tumor microenvironment (TME). Moreover, intratumoral LP treatment led to systemic abscopal antitumor effects in non-injected distant tumors. Notably, LP treatment combined with ɑPD-1 and ɑCTLA-4 further enhanced the efficacy of monotherapy, resulting in complete tumor regression and prolonged overall survival. Furthermore, LP-based combination immunotherapy elicited durable antitumor immunity with tumor-specific immune memory in colon cancer and melanoma. Conclusions: Our study demonstrated that intratumoral LP treatment improves the innate and adaptive antitumor immunity within the TME and enhances the efficacy of αPD-1 and αCTLA-4 immune checkpoint blockade.